Effects of Tea (Camellia sinensis) Addition on Soaking Salted Eggs of Organoleptic Quality, Protein Content, Fat Content, and Ash Content - Ardhi, Ferdyansyah Prasetya; Amertaningtyas, Dedes; Wati, Anif Mukaromah; Saleha, Rischa Amalia (Jurnal Ilmu dan Teknologi Hasil Ternak, 2024)
This research aimed to determine the effect of tea essence on the organoleptic quality, protein content, fat content, and ash content of salted eggs. The research material consisted of salted eggs with different percentages of tea essence added tea essence. The method used an experiment with 4 treatments and 4 replications. The treatments given were (P1) 25%, (P2) 50% and (P3) 75% with the addition of tea essence in different percentages and without the addition of tea essence (P0) as a control treatment. The variables measured include organoleptic quality, fat content, protein content and ash content. Data were analyzed using a Completely Randomized Design (CRD). The results showed that the addition of tea essence did not have a significantly different effect (p > 0.05) on the fat content, protein content, ash content, taste, aroma and color of salted eggs. Average fat content value of 10.91-10.37%, protein content of 12.05-12.43%, ash content of 1.62-1.54%, taste score of 3.75-3.65, aroma score of 3.50-3.40, and color score of 3.60-3.90. It can be concluded that the best treatment was obtained by adding 25% tea essence with an ash content value of 2.03%, a fat content of 11.40%, aroma score of 3.55, and the best treatment was obtained by   adding 75% tea essence with a protein content value of 12.43%, a color score of 3.90, and taste score of 3.75.